Navigating transnational motherhood and economic agency: the transformation of gender roles among Indonesian female migrant workers - Tri Sandy Mareta; Fatmariza Fatmariza; Azmi Fitrsia; Delmira Syafrini (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study examines the dual roles of female migrant workers in Kuala Merbau Village as economic providers and family caregivers within transnational family arrangements. The study draws on push-pull migration theory, feminization of migration, and transnational motherhood to analyse how migration reshapes gender relations and caregiving practices in rural households. A qualitative descriptive approach was employed involving 15 informants consisting of female migrant workers, family members, and community leaders selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analysed using thematic analysis with triangulation techniques. The findings show that women’s migration is primarily driven by unstable local employment and household economic insecurity, particularly related to children’s educational needs. After migrating, women become the primary income earners through remittances, resulting in shifts in household economic and caregiving roles. Although caregiving responsibilities are delegated to husbands or extended family members, migrant women continue to perform emotional and maternal responsibilities through long-distance communication. The study also finds that prolonged family separation generates emotional burdens, including guilt, anxiety, and psychological stress, while strong dependence on remittances creates household economic dependency. This study demonstrates that female migration simultaneously produces economic empowerment and emotional vulnerability, revealing how gendered caregiving responsibilities persist despite women’s increasing economic roles within transnational families.